Avaliação da qualidade de vida e fatores associados de pessoas com urostomias - SILVA, Ingrid Loyane Bezerra Balata (2024)
Urostomies are surgically created stomas to preserve kidney function in people with pathologies involving the kidneys, ureters, bladder and urethra. The main causes are shunts through catheters, most commonly to relieve obstructions to urinary flow. In this way, nursing has an essential role in providing assistance to people with ostomies, in order to seek self-care, so that they can develop self-perception and consequently a good quality of life. From this perspective, the study aims to analyze the quality of life of people with urostomies and associated factors in the State of Maranhão. A descriptive and analytical study was carried out, with a quantitative approach that analyzed people with urostomies in the State of Maranhão. The study population was all people with urostomies registered in the Orthosis and Prosthetics Service of the Municipal Health Department of São Luís and in the urology outpatient clinic of the University Hospital of the Federal University of Maranhão until December 2022, totaling 110 people, the sample included with 33 participants. The research instruments correspond to sociodemographic, clinical and quality of life questionnaires COH-QOL-OQ. Among people with urostomies, the majority are male (51.6%), aged between 51 and 70 years old (51.50%), self-declared as having brown color/race (57,6%), incomplete primary education ( 45.4%), the cause of the stoma is cancer (54.54%), the pouch change is carried out by the person with the stoma (54.54%), they do not practice physical activities (81.82%), they do not have drinking habits alcohol or drugs (72.73%) and eat fruits or vegetables every day (51.50%). Participants had positive impacts on their physical, psychological and spiritual well-being, while they had low scores on social well-being. Regarding the physical well-being domain, higher averages were obtained in the items of physical strength (5.15), sleep interruption (5.48) and bag leakage (5.0). The psychological domain was satisfactory for quality of life, with emphasis on the items Depression (1.6), Satisfaction/Pleasure in Life (7.5), Memory (8.1) and Satisfaction with Appearance (7.6). There was an impact on the social well-being of the people in the study, making it possible to highlight the positive impact on Difficulty meeting new people (2.5) and Isolation (1.5) with low scores, in addition to Support from friends (8.5) and Privacy when caring for a stoma (9.3). The scores were positive for the quality of life of people with urostomies in terms of spiritual well-being, but had a low number for Positive Changes (4.9). There was an association with low education (illiteracy) and changes in physical, psychological and social well-being. Furthermore, people without a support network are associated with psychological impacts on quality of life and the cause of the stoma (cancer) and length of stay (definitive) are associated with impacts on quality of life in terms of physical well-being, psychological and social. The research hopes to encourage new studies of people with urostomies, in addition to encouraging professionals specialized in the area to provide comprehensive care, pointing out public managers' attention to the demands of this group.